Pegembangan Media Mind Mapping Digital Berbasis OBE Untuk Meningkatkan Berpikir Kritis Mahasiswa - Meiriza, Mica Siar; Purba, Jelita Angeli; Napitu, Krisentia Angelina; Tamba, Agnes Anggreni; Dalimunthe, Nayla Ahlami (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – Students’ critical thinking skills in the History of Socialist Economic Thought course are still low because learning is mostly lecture-based and less interactive. Therefore, innovative media are needed to make learning more engaging and outcome oriented. This study aims to develop Outcome-Based Education (OBE)-based Digital Mind Mapping media and examine its feasibility and effectiveness in improving students’ critical thinking skills.Method – The study used a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects were 34 students of the Economics Education Study Program at Universitas Negeri Medan. Data were collected using tests (one group pretest–posttest) and non-test instruments such as observation, interviews, and questionnaires.Findings – Validation results showed that the media was very feasible, with an average score of 87.14% from material, media, and design experts. Effectiveness testing obtained an N-Gain value of 0.58 (moderate) and Cohen’s d of 2.26 (very large effect), proving that the media effectively enhanced students’ critical thinking. Research Implications – The findings strengthen the constructive alignment principle of OBE and support Mayer’s multimedia learning theory, emphasizing that visual and interactive media can improve students’ engagement and higher-order thinking skills.